2001
DOI: 10.1073/pnas.041620798
|View full text |Cite
|
Sign up to set email alerts
|

CA1-specific N -methyl- d -aspartate receptor knockout mice are deficient in solving a nonspatial transverse patterning task

Abstract: In both humans and animals, the hippocampus is critical to memory across modalities of information (e.g., spatial and nonspatial memory) and plays a critical role in the organization and flexible expression of memories. Recent studies have advanced our understanding of cellular basis of hippocampal function, showing that N-methyl-D-aspartate (NMDA) receptors in area CA1 are required in both the spatial and nonspatial domains of learning. Here we examined whether CA1 NMDA receptors are specifically required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 25 publications
4
48
1
Order By: Relevance
“…Also, Rondi-Reig et al (2001) tested mice lacking CA1 NMDA receptors on the transverse patterning problem that required simultaneous acquisition of three odor discriminations comprising the transverse patterning problem contrasted with concurrent learning of three simple odor discriminations. They found that CA1 NMDA receptor knock-out mice were impaired in solving the transverse patterning odor discrimination compared with normal performance on the non-overlapping (elemental) concurrent odor discriminations (but see Bussey et al, 1998).…”
Section: Transverse Patterning Discriminationsmentioning
confidence: 99%
“…Also, Rondi-Reig et al (2001) tested mice lacking CA1 NMDA receptors on the transverse patterning problem that required simultaneous acquisition of three odor discriminations comprising the transverse patterning problem contrasted with concurrent learning of three simple odor discriminations. They found that CA1 NMDA receptor knock-out mice were impaired in solving the transverse patterning odor discrimination compared with normal performance on the non-overlapping (elemental) concurrent odor discriminations (but see Bussey et al, 1998).…”
Section: Transverse Patterning Discriminationsmentioning
confidence: 99%
“…Learning is usually investigated by showing that an animal can perform a previously unfamiliar task with reliability greater than what would be expected by chance. The ability of an animal to learn a new task is commonly tested to study how brain lesions (Whishaw and Tomie, 1991;Roman et al, 1993;Dias et al, 1997;Dusek and Eichenbaum, 1997;Wise and Murray, 1999;Fox et al, 2003), attentional modulation (Cook and Maunsell, 2002), genetic manipulations (Rondi-Reig et al, 2001), or pharmacological interventions (Stefani et al, 2003) alter learning. Characterizations of the learning process are also important to relate an animal's behavioral changes to changes in neural activity in target brain regions (Jog et al, 1999;Wirth et al, 2003).…”
mentioning
confidence: 99%
“…Learning is typically studied by showing that after a set of trialand-error attempts, a subject is able to execute an unfamiliar task more reliably than chance would predict. The ability of an animal to learn a new task is frequently studied to characterize how attentional modulation (Cook and Maunsell 2002), genetics (Rondi-Reig et al 2001), brain lesions (Roman et al 1993;Whishaw and Tomie 1991;Dusek and Eichenbaum 1997;Fox et al 2003;Wise and Murray 1999), or drug interventions (Stefani et al 2003) affect learning. Accurate characterizations of learning are also important to relate changes in behavior to changes in neural activity in specific brain regions (Jog et al 1999;Law et al 2005;Wirth et al 2003).…”
Section: Introductionmentioning
confidence: 99%